2019
DOI: 10.1177/0145721719844547
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Technologically Enhanced Peer Support in Improving Glycemic Management Among Predominantly African American, Low-Income Adults With Diabetes

Abstract: Purpose-This study's purpose is to examine whether a peer coaching intervention is more effective in improving clinical outcomes in diabetes when enhanced with e-Health educational tools than peer coaching alone. Methods-The effectiveness of peer coaches who used an individually tailored, interactive webbased tool (iDecide) was compared with peer coaches with no access to the tool. 290 Veterans Affairs patients with A1c>8.0% received a six-month intervention with an initial session with a fellow patient traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
2
27
0
1
Order By: Relevance
“…In such an analysis, a conceptual model is created that hypothesizes potential targets, or mediators, along the mechanistic pathway that an intervention must include in order to be successful in achieving the desired outcome. In the previously mentioned RCT by Heisler et al [ 23 ], participants had at least weekly contact with a fellow patient with T2D who had received a 2-hour training session with a focus on motivational interviewing, including active listening skills, rolling with resistance, enhancing change talk, goal setting, and action planning. During these sessions, peer coaches helped participants develop and follow up on weekly action steps to meet the participants’ defined behavioral goals.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In such an analysis, a conceptual model is created that hypothesizes potential targets, or mediators, along the mechanistic pathway that an intervention must include in order to be successful in achieving the desired outcome. In the previously mentioned RCT by Heisler et al [ 23 ], participants had at least weekly contact with a fellow patient with T2D who had received a 2-hour training session with a focus on motivational interviewing, including active listening skills, rolling with resistance, enhancing change talk, goal setting, and action planning. During these sessions, peer coaches helped participants develop and follow up on weekly action steps to meet the participants’ defined behavioral goals.…”
Section: Methodsmentioning
confidence: 99%
“…Peer support interventions have been successful in improving both glycemic outcomes and psychosocial outcomes, including diabetes distress, and are an attractive, low-cost approach for health care systems [ 20 - 22 ]. A recently published randomized controlled trial (RCT) of peer support versus technology-enhanced peer support for primarily African American veterans with T2D who receive care at an urban Veterans Affairs (VA) health center published by Heisler et al [ 23 ] demonstrated that the peer coach model they evaluated, both with and without technology enhancement, was effective at improving glycemic control and reducing diabetes distress over the 6-month intervention period.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations